The Cambridge companion to the book of Isaiah - Hays, Christopher B. (Cambridge companions to religion, 2024)
"The Cambridge Companion to Isaiah is aimed at students, teachers, and interested readers of all kinds who would like an up-to-date and reliable guide to the book of Isaiah. It includes diverse perspectives from leading scholars all over the world, and a wide range of methodological approaches"--